DEVELOPING A DATA ELEVATION MODEL (DEM) BASED- MAP OF BELAKANG PADANG ISLAND, BATAM - Ade Jaya Saputra; Yusra Aulia Sari; Jody Martin Ginting; Al Husni; Marvin Tandedi; Tohmas Saputra; Muhammad Alfi Wahyudi (Universitas Internasional Batam, 2022)
Belakang Padang is one of the islands located in Batam City hinterland area. It is known as “Pulau Penawar Rindu” and has become one of tourism interest in Batam City. Even though it has become a tourism interest, Belakang Padang island lacks a map for tourist navigation. This community service aim to help Belakang Padang island by making a map based on data elevation model (DEM). By using ArcGIS as the data processing, a navigation map is created as a tourism property. The map contains the basic information of the island such as transportation route, geographical element, and place of interest. Future project can be done by expanding the information provided by the map.